A practical method for quantifying dose in bone and lung using TLDs when using 6 and 15 MV photon beams. (6th March 2020) - Sarigul, Neslihan; Surucu, Murat; Reft, Chester; Malin, Martha; Yegingil, Zehra; Aydogan, Bulent
Abstract: This paper presents a practical method for converting dose measured with thermoluminescent dosimeters (TLD) to dose in lung and bone for 6 MV and 15 MV photon beams. Monte Carlo (MC) simulations and Burlin cavity theory calculations were performed to calculate, the dose-to-TLD to dose-to-medium conversion factor. A practical method was proposed for converting TLD-measured-dose to dose-in-medium using the TLD dose calibration in water and dose-to-medium to dose-to-water conversion factor. Theoretical calculations for were performed using photon spectrum weighted parameters and were compared with MC simulations. Verification of the proposed method was done using phantoms having either bone or lung equivalent slabs stacked in between solid water slabs. Percent depth dose (PDD) curves were measured using 0.089 cm thick LiF:Mg, Ti (TLD-100) dosemeters placed at various depths within these phantoms. They were then corrected with factors using the proposed dose conversion method, and were compared with the MC simulations. For 6 MV beam, the MC calculated factors were 0.942 and 1.002 for bone and lung, and for 15 MV it was 0.927 and 1.005 for bone and lung, respectively. The difference between the MC simulated and spectrum weighted theoretical factors were within 3% for both lung and bone. The PDD curves measured with TLD-100 chips that were corrected using the proposed method agreed well within 1.5% of the MC simulated PDD curves for both the water/lung/water and water/bone/water (WBW) phantoms. The dose-to-medium correction using MC simulated is convenient, easy, and accurate. Therefore, it can be used instead of Burlin cavity theory, especially in media with high atomic numbers such as bone for accurate dose quantification.